PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KEARSIPAN DI MASA PANDEMI COVID-19 - Laura Enjelika Gultom, - (2022)
This study aims to determine the effect of online learning on student learning out-comes in Archiving Subjects during the Covid-19 Pandemic Period. The research method uses quantitative research. The data collection technique used a 5-scale questionnaire rating scale model. Respondents were 146 students of Pasundan 1 Vocational High School (SMK) Bandung City. The data analysis technique used simple regression. The results showed: (1) online learning during the Covid-19 pandemic at SMK Pasundan 1 Bandung City was in the quite effective category; (2) student learning outcomes during the Covid-19 pandemic at SMK Pasundan 1 Bandung City were in the medium category; and (3) online learning has a positive and significant effect on student learning outcomes.